A red-NIR fluorescent probe for rapid and visual detection of acrolein. Issue 72 (23rd August 2022) - Xu, Hai; Zhang, Chen; Zhang, Yu-Qing; Suo, Sheng-Nan; Wang, Ya-Wen; Peng, Yu
Abstract : A red-NIR turn-on fluorescent probe has been developed for rapid, sensitive and colorimetric detection of toxic acrolein. Abstract : A novel red-NIR probe (SWJT-8) for detecting acrolein by utilizing the Michael addition reaction was developed. SWJT-8 exhibits a series of unique advantages, such as colorimetric discrimination, high selectivity and the fastest response. And this probe has been successfully applied to the detection of intracellular acrolein.